2022
DOI: 10.1093/sleep/zsac050
|View full text |Cite
|
Sign up to set email alerts
|

Clinical polysomnographic methods for estimating pharyngeal collapsibility in obstructive sleep apnea

Abstract: Study Objectives Obstructive sleep apnea has major health consequences but is challenging to treat. For many therapies, efficacy is determined by the severity of underlying pharyngeal collapsibility, yet there is no accepted clinical means to measure it. Here we provide insight into which polysomnographic surrogate measures of collapsibility are valid, applicable across the population, and predictive of therapeutic outcomes. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 32 publications
0
18
0
Order By: Relevance
“…Indeed, support for this argument can also be gleaned directly from the polysomnographic data presented by Kinouchi et al In their study, the proportion of respiratory events 9 that were hypopnoeas (Fhypopnoeas) was approximately 40%. By contrast, the Fhypopnoeas in the Taranto‐Montemurro et al trial was ~85%.…”
mentioning
confidence: 75%
See 1 more Smart Citation
“…Indeed, support for this argument can also be gleaned directly from the polysomnographic data presented by Kinouchi et al In their study, the proportion of respiratory events 9 that were hypopnoeas (Fhypopnoeas) was approximately 40%. By contrast, the Fhypopnoeas in the Taranto‐Montemurro et al trial was ~85%.…”
mentioning
confidence: 75%
“…By contrast, the Fhypopnoeas in the Taranto‐Montemurro et al trial was ~85%. Notably, Vena et al have recently demonstrated that this polysomnographic measure can be used as a surrogate measure for airway collapsibility (i.e., the lower the proportion, the more collapsible the airway) 9 . Furthermore, while there was no clear reduction in the total AHI in the Kinouchi study, there was a significant increase in the fraction of respiratory events that were hypopneas (or reduction in proportion of apnoeas).…”
mentioning
confidence: 95%
“…V ACTIVE was defined as the level of ventilation at maximum drive (i.e., arousal threshold). V MIN 20 was the ventilation at the lowest drive (i.e., first decile). All traits, except for loop gain, which is dimensionless, were expressed as percent of V EUPNOEA , namely unobstructed ventilation during sleep at normal ventilatory drive (see Figure 2, right panel).…”
Section: Methodsmentioning
confidence: 99%
“…V passive is the level of ventilation at eupneic ventilatory drive and reflects the passive airway, while V active is the ventilation achieved just prior to the termination of a respiratory event when V drive is at its peak and the airway is maximally stimulated. The V min provides an alternative measure of collapsibility and is based on the ventilation observed at the minimal level of V drive (calculated from the lowest decile instead of median V eupnea , Vena et al, 2022 ). A lower value denotes a more collapsible airway.…”
Section: Methodsmentioning
confidence: 99%
“…How to cite this article: Thomson, L. D. J., Landry, S. A., Joosten, S. A., Mann, D. L., Wong, A-M, Cheung, T., Adam, M., Beatty, C. J., Hamilton, G. S., & Edwards, B. A.…”
Section: Funding Informationmentioning
confidence: 99%